Teaching the EU : fostering knowledge and understanding in the Brexit age - Visvizi, Anna; Field, Mark; Pachocka, Marta (Emerald studies in higher education, innovation and technology., 2021)
Against the backdrop of disintegrative tendencies in the EU, where Brexit perhaps most profoundly captures the spirit of current developments in the EU, this book offers a detailed understanding of the key issues, challenges, and opportunities that educators across Europe and beyond encounter on a daily basis when teaching EU-related course content at higher education institutions. Written by a team of international academics and practitioners engaged with teaching, researching, and explaining European integration to successive generations of students, this edited collection showcases expert voices on the issues and developments central in the debate on how to teach the EU efficiently today. Using a wide variety of case studies, the chapters examine how novel approaches to teaching and learning, and especially technology-enhanced tools and methods, can lead to better teaching and learning outcomes in the Brexit age. A cutting-edge collection of insights from experts teaching and researching the EU, this book will serve as a timely resource for educators, researchers, administrators, and decision-makers.